2015
DOI: 10.1002/2015gl063147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the inertial dissipation method within boundary layers using numerical simulations

Abstract: We evaluated the accuracy of the inertial dissipation method to estimate the rate of dissipation of turbulent kinetic energy within boundary layers by performing well‐resolved numerical simulations of turbulent channel flows and comparing the dissipation calculated directly from the data, with that deduced from the frequency spectra. The convection velocity, commonly used to convert frequency spectra into wave number spectra is found to be larger than the local mean velocity by approximately a factor of 2 near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
1
12
1
Order By: Relevance
“…(c) Ratio between vertical and along‐stream Kolmogorov constants determined in our study in comparison with the values of Jabbari et al . []. The vertical solid line denotes the value of 4/3 as generally used in the IDM.…”
Section: Boundary Layer Characterization By Stepwise Profilingcontrasting
confidence: 43%
See 3 more Smart Citations
“…(c) Ratio between vertical and along‐stream Kolmogorov constants determined in our study in comparison with the values of Jabbari et al . []. The vertical solid line denotes the value of 4/3 as generally used in the IDM.…”
Section: Boundary Layer Characterization By Stepwise Profilingcontrasting
confidence: 43%
“…We found that the use of the inertial dissipation method using the generally accepted Kolmogorov constants for the determination of ε under these conditions is not valid any more. Our study provides evidence that the constants determined by numerical modeling [ Jabbari et al ., ] are more appropriate in the close vicinity of the SWI in natural systems. In addition, we were able to observe the viscous boundary layer and to find indications of a double logarithmic layer in the very close vicinity of the SWI‐ an achievement which would not have been possible with standard ADVs with a spatial resolution of about 1.5 cm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this method, the correlation function between two points with the vertical separation distance r (i.e., 3 cm bin size) SF()z,r=true()ub()zub()z+r2¯ is related to the dissipation by SF( z , r ) = ∝ ε 2/3 r 2/3 within the inertial subrange, where is the Kolmogorov (2/3) constant, and ub is the in‐beam fluctuating velocity obtained from Reynolds averaging each burst (the over‐bar denotes the time average). To account for the anisotropy from the bed shear stress (Jabbari et al ), we applied the anisotropy adjusted constants (Jabbari et al ), where is a function of the normalized distance from the bed z + = zu * / ν , where u * is the shear velocity. To compute u * , the profiles of the mean horizontal velocity um=u2+v2 were fit to the logarithmic law‐of‐the‐wall over the constant stress layer by the least‐square‐fitting method (e.g., Jabbari ; Valipour et al ).…”
Section: Methodsmentioning
confidence: 99%